2003
DOI: 10.1037/0278-6133.22.6.559
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Cardiovascular and Metabolic Disease and Cognition in Very Old Age: Cross-Sectional and Longitudinal Findings From the Berlin Aging Study.

Abstract: This study documented findings on the relation between cognitive functioning (perceptual speed, memory, fluency, and knowledge) and cardiovascular and metabolic disease in a sample of very old adults (ages 70 and older), both cross-sectionally (n=516) and longitudinally (n=206) in a 4-year follow-up. After age, SES, sex, and dementia status were controlled for, 4 diagnoses were negatively associated with cognition: congestive heart failure, stroke, coronary heart disease, and diabetes mellitus, with a joint ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
80
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 45 publications
9
80
2
1
Order By: Relevance
“…Two out of the four AP studies did find that AP increased the risk of dementia or possible dementia/mild cognitive impairment [19,24], whereas the other two studies did not find an association [22,23]. For the CHD compound, three studies did not find a relation with cognitive decline or decline to dementia/mild cognitive impairment [22,25,27], whereas one study found that CHD was a significant predictor of vascular dementia [26].…”
Section: Prospective Cohort Studiesmentioning
confidence: 80%
See 4 more Smart Citations
“…Two out of the four AP studies did find that AP increased the risk of dementia or possible dementia/mild cognitive impairment [19,24], whereas the other two studies did not find an association [22,23]. For the CHD compound, three studies did not find a relation with cognitive decline or decline to dementia/mild cognitive impairment [22,25,27], whereas one study found that CHD was a significant predictor of vascular dementia [26].…”
Section: Prospective Cohort Studiesmentioning
confidence: 80%
“…For AP, two studies found a significant association with poor cognitive functioning [34,37], whereas one study found no association with mild cognitive impairment [36]. For the CHD compound studies, three studies found a significant association with poor cognitive functioning [27,37,40], one study found no relation with cognitive function or cognitive impairment [38], and one study found a significant association with dementia risk [39].…”
Section: Case-control Studiesmentioning
confidence: 90%
See 3 more Smart Citations